Influence of Two Desmodium Species Root Exudates on Haustorium Initiation and Attachment in Striga hermonthica (Del.) Benth (University of Khartoum Journal of Agricultural Sciences, 2023)
Striga hermonthica is a parasitic weed that causes significantyield losses in many important crops and affects the livelihood of millionsof people worldwide. A study was undertaken to examine the effects ofDesmodium. uncinatum (Jacq.) DC and D. dichotomum (Klein) DC rootexudates on initiation of haustorium and attachment of S. hermonthica. Aseries of laboratory experiments was conducted at the Gezira ResearchStation, Wad Medani, Sudan. D. uncinatum and D. dichotomum rootexudates, applied 24 hours subsequent to GR 24, a synthetic germinationstimulant, or simultaneously with it, did not induce haustorium initiation.D. uncinatum and D. dichotomum curtailed striga attachment to sorghumroots.
Keywords: Striga; Desmodium spp; root exudates; haustorium initiation; attachment